2011
DOI: 10.1248/bpb.34.655
|View full text |Cite
|
Sign up to set email alerts
|

The Enantiomers of Etodolac, a Racemic Anti-inflammatory Agent, Play Different Roles in Efficacy and Gastrointestinal Safety

Abstract: The therapeutic effects of non-steroidal anti-inflammatory drugs (NSAIDs) include anti-pyretic, analgesic and anti-inflammatory effects, while their adverse effects are primarily gastrointestinal (GI) and renal toxicity. The major therapeutic and adverse effects are mediated by the inhibition of cyclooxygenase (COX), which catalyzes the rate-limiting step in the formation of prostanoids from arachidonic acid. [1][2][3] There are two membrane-bound COX isoenzymes, the constitutively expressed COX-1 and the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Its therapeutic effects are due to its ability to inhibit prostaglandin synthesis (“as discussed by Inoue et al [1]”). Prostaglandins are the chemicals which are responsible for pain and the fever and tenderness that occur with inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Its therapeutic effects are due to its ability to inhibit prostaglandin synthesis (“as discussed by Inoue et al [1]”). Prostaglandins are the chemicals which are responsible for pain and the fever and tenderness that occur with inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the change in mucus secretion and the acid/mucus ratio did not differ significantly between those individuals who had severe mucosal injury and those who did not (such as in those with MLS of ≥ 4) (data not shown), there could be other mechanisms underlying the apparent differences in the severity of the mucosal injury between individuals administered naproxen and those administered etodolac. Interestingly, a recent study reported that etodolac consists of 2 enantiomers, S-and R-etodolac, and that R-etodolac reduced HCl/ethanolinduced gastric damage in rats (Inoue et al 2011). The gastroprotective effects of R-etodolac may also be associated with a modulation of the gastric secretory function.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that etodolac shows an antiallodynic effect in a mouse model of neuropathic pain [3]. The effect depends on the S -enantiomer of etodolac and appears to be mediated by a COX-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that etodolac, a nonsteroidal anti-inflammatory drug (NSAID) and selective cyclooxygenase-2 (COX-2) inhibitor, attenuates allodynia in a mouse model of neuropathic pain [2]. The mechanism of the antiallodynic effect of etodolac has not yet been established, but COX inhibition is unlikely to be involved because other COX inhibitors do not attenuate the allodynia [2,3]. …”
Section: Introductionmentioning
confidence: 99%